African-led health research and capacity building- is it working? - Victoria O. Kasprowicz; Denis Chopera; Kim Darley Waddilove; Mark A. Brockman; Jill Gilmour; Eric Hunter; William Kilembe; Etienne Karita; Simani Gaseitsiwe; Eduard J. Sanders; Thumbi Ndung’u (BMC Public Health, 2020)
Abstract Background Africa bears a disproportionately high burden of globally significant disease but has lagged in knowledge production to address its health challenges. In this contribution, we discuss the challenges and approaches to health research capacity strengthening in sub-Saharan Africa and propose that the recent shift to an African-led approach is the most optimal. Methods and findings We introduce several capacity building approaches and recent achievements, explore why African-led research on the continent is a potentially paradigm-shifting and innovative approach, and discuss the advantages and challenges thereof. We reflect on the approaches used by the African Academy of Sciences (AAS)-funded Sub-Saharan African Network for TB/HIV Research Excellence (SANTHE) consortium as an example of an effective African-led science and capacity building programme. We recommend the following as crucial components of future efforts: 1. Directly empowering African-based researchers, 2. Offering quality training and career development opportunities to large numbers of junior African scientists and support staff, and 3. Effective information exchange and collaboration. Furthermore, we argue that long-term investment from international donors and increasing funding commitments from African governments and philanthropies will be needed to realise a critical mass of local capacity and to create and sustain world-class research hubs that will be conducive to address Africa’s intractable health challenges. Conclusions Our experiences so far suggest that African-led research has the potential to overcome the vicious cycle of brain-drain and may ultimately lead to improvement of health and science-led economic transformation of Africa into a prosperous continent.